Nasal deformity correction with nasal prosthesis - Megha Sahu; Monal Karkar; Vaibhav Rama Subramaniam; Gosla Srinivas Reddy (Wolters Kluwer Medknow Publications, 2022)
Nasal deformities can vary in the form of severity. Several different factors such as congenital, burn and traumatic nasal fractures or soft-tissue injury/loss, neoplastic: defects resulting from surgery for the treatment of cancers causing compromise the structural architecture and functional framework of the nose. This case report describes the prosthetic rehabilitation of two female patients, one who was reported with congenital arrhinia and another one who had accidental electrical burns of the face. The surgeon's team as well as the maxillofacial prosthetics team discussed the treatment options with the parents and decided to rehabilitate with a nasal prosthesis. This clinical report is imparting an accessible and economic method for prosthetic rehabilitation of a patient.